Pyruvate-based peritoneal dialysate preserves neutrophilic oxygen consumption - Zhou Fang-Qiang; Yu Alex W (Acta Pharmacologica Sinica; Vol 19, No 3 (May 1998): Acta Pharmacologica Sinica, 2016)
AIM: To investigate effects of pyruvate- or lactate-based peritoneal dialysis solutions (P-PDS or L-PDS) on neutrophilic oxygen consumption and the role of the extracellular pH (pHe) in cells' oxygen uptake. METHODS: Human neutrophils were incubated in P-PDS or L-PDS containing pyruvate or lactate 35-38 mmol.L-1 at various pHe, respectively. Oxygen consumption rates by opsonized zymosan (OZ)-stimulated cells were measured polarographically, using a Clark-type oxygen electrode. RESULTS: L-PDS at an initial pH 5.2 dramatically inhibited the rate of oxygen consumption (2.2 nmol.min-1/10(6) cells) by neutrophils, while the equally acidic P-PDS markedly improved the rate (6.4 nmol.min-1/10(6) cells) (P < 0.01). However, P-PDS at pHe 5.2 severely impaired the rate by cells, the same as pHe 5.2 L-PDS. CONCLUSION: P-PDS preserved an oxygen consumption rate by OZ-stimulated human neutrophils, but in an acidi milieu it comparably deteriorated the ability of cells to consume oxygen, indicating that the pHe of PDS plays an essential role in cellular oxidative metabolism. The superior biocompatibility of an acidic P-PDS was associated with its lower buffering capacity.